Tannins Enriched Fraction of Emblica officinalis Fruits Alleviates High-Salt and Cholesterol Diet-Induced Cognitive Impairment in Rats via Nrf2-ARE Pathway - Ibraheem Husain; Mohd Akhtar; Tushar Madaan; Divya Vohora; Malik Z. Abdin; Mohammad Islamuddin; Abul K. Najmi (Frontiers Media S.A., 2018)
Modern diets containing high quantities of salt and cholesterol have exhibited to cause a considerable effect on our health. Such diets, when consumed in the long term, have also shown to be a precursor to several disorders such as the metabolic disorder and consequently, various other diseases, including cognitive deficits. In the present study, we used a high salt and cholesterol diet (HSCD) to induce cognitive impairment in rats and also investigated the pharmacological action of tannins enriched fractions of Emblica officinalis (EOT) - a fruit that has been traditionally used for the treatment of numerous disorders for centuries. Significant alterations in MDA, GSH, TBARS, GPx, mitochondrial ATP, and mitochondrial membrane potential levels were observed in rats fed HSCD, which indicated presence of oxidative stress. Moreover, classic signs of cognitive impairment and deficits in spatial learning and memory were observed in the neurobehavioral tests. E. officinalis tannins exhibited good affinity to Nrf2 receptors in in silico studies, significantly reversed the changes in the aforementioned biomarkers of oxidative stress which were altered in the model group, as well as improved the performance of rats in Morris water maze task. Our results also reflected that EOT supplementation significantly increased the expression of Nrf2 in the CA1 region of hippocampus and cortex. Additionally, TUNEL assay indicated that EOT supplementation led to reversal of DNA fragmentation and apoptosis caused by HSCD. Immunohistochemical analysis and western blot further revealed a surge in the nuclear location of Nrf2. Through our study, we have demonstrated that cognitive impairment can be caused in rats via HSCD as a result of the oxidative stress induced by the same. Additionally, we have investigated a novel mechanism of action for EOT (which strongly suggests to be via the Nrf2-ARE pathway) and demonstrated that it has the potential to be used in the treatment of cognitive impairment.